Climate change and forced migrations: An effort towards recognizing climate refugees. Issue 84 (August 2017) - Berchin, Issa Ibrahim; Valduga, Isabela Blasi; Garcia, Jéssica; de Andrade Guerra, José Baltazar Salgueirinho Osório
Abstract: The scientific community has long urged for the broadening of the refugee term, which remains identical since the 1951 Refugee Convention, despite strong evidence showing connections between forced migration and climate change. Even though the concept of climate and environmental refugees is not legally recognized, the discussion concerning these definitions is increasing. Furthermore, with the intensification of global climate change, a more specific subcategory of refugees began to be popularized: climate change refugees. A climate change refugee is any person who has been forced to leave their home, or their country, due to the effects of severe climate events, being forced to rebuild their lives in other places, despite the conditions to which they are subjected.